Performance boost of dye-sensitized solar cell by using barium titanate as a compact layer - Fiter, Logeswary; Shafie, Suhaidi; Sulaiman, Yusran (Elsevier, 2024)
Perovskite oxides are a versatile material that has the potential to replace the conventional TiO2 in dye-sensitized solar cells (DSSCs) as a compact layer. Perovskite-type oxide, barium titanate (BTO) as a compact layer was prepared using facile spin coating. Upon the addition of the BTO compact layer, the leakage current caused by the recombination of electrons is reduced. Thus, BTO can be used as a good blocking material to suppress the back electron movement in the DSSCs from the glass substrate to the iodide electrolyte. Besides, the incorporation of the BTO compact layer has increased the adsorption of dye to generate photogenerated charge carriers when compared to the bare TiO2 photoanode, resulting in an increment in Jsc of the solar cell. The rise in the resistance caused by the charge transfer (Rct2) of the device with the BTO compact layer is evidence of the improvement of the charge transfer in the metal oxide/dye/electrolyte interface. Thus, the DSSC containing the BTO compact layer exhibited an improvement in solar cell efficiency to 4.92 %.